COVID‐19 and nursing research across five countries/regions: Commonalities and recommendations. Issue 5 (21st July 2021) - Im, Eun‐Ok; Sakashita, Reiko; Oh, Eui Geum; Tsai, Hsiu‐Min; Chen, Ching‐Min; Lin, Chia‐Chin; McCauley, Linda
Abstract: With the recent impact by the COVID‐19 pandemic, nursing research has gone through unexpected changes across the globe. The purpose of this special report is to present the commonalities in the impact of the COVID‐19 pandemic on nursing research across four countries, including the United States, South Korea, Japan, and Taiwan, and one region, that is, Hong Kong, and to make recommendations for future nursing research during the immediate postpandemic period and future pandemic situations. To identify the commonalities, seven researchers/leaders from the five countries/regions had discussions through 3 days of an international workshop. The content for this discussion paper derived from: (a) the exemplars/cases of the COVID‐19 impact on the research process, (b) researchers/leaders' presentations on the COVID‐19 impact, and (c) memos from the workshop. The materials were analyzed using a simple content analysis. The commonalities included: (a) "a heavy emphasis on teaching and fluctuating productivity, " (b) "increased funding opportunities and governmental support, " (c) "gendered experience complicated by professional differences, " (d) "delays and changes/modifications in research process, " (e) "limited research settings and difficulties in getting access, " and (f) "increased online dissemination activities with positive changes in the image of nursing." With all collective wisdom that nurse researchers have obtained during the COVID‐19 pandemic, nursing research will evolve again for the successful future of the nursing discipline.